Enacting Media. An Embodied Account of Enculturation Between Neuromediality and New Cognitive Media Theory - Fingerhut, Joerg (Frontiers in Psychology, 2021)
This paper argues that the still-emerging paradigm of situated cognition would benefit from a more systematic perspective on media to capture the enculturation of the human mind. By virtue of being media, cultural artifacts present experiential models for our embodied minds to latch onto. The paper identifies central references to external media within embodied, extended, enactive, and predictive approaches to cognition, which remain underdeveloped in terms of the profound impact that media have on us. To capture this impact, I propose an account of artifactual habits that sees such habits as media-structured enactive ways of bringing forth meaning. We apply such habits, for instance, when seeing a picture or perceiving a movie. They become established through a process of reciprocal adaptation between media artifacts and organisms and the define the range of viable actions within such a media ecology. In an artifactual habit, we become dynamically attuned to a specific media artifact (e.g., a TV series, a picture, a text, or even a city) that engages us. Both the switching between habits and the dynamical adjustments within a habit requires a more flexible neural architecture to sustain our media interactions than is addressed by classical cognitive neuroscience. To detail how neural and media processes complement each other and how they interlock, I will introduce the concept of neuromediality and discuss an embodied, action-oriented version of predictive processing. The way I construe it, such a theory could centrally contribute to the externalization of the mind by treating media themselves as generative models of the world. After a short primer on general media theory, I discuss examples of media engagements within cognitive media theory in three domains: pictures and moving images; digital media; architecture and the built environment. This discussion demonstrates the need for a new cognitive media theory based on enactive artifactual habits—one that will help us gain perspective on the continuous re-mediation of our mind.